Physiological Response of Kappaphycus alvarezzi Seaweed to Ice-Ice Disease Exposure - Lalu Arip Fathurrahman; Ernin Hidayati (Samota Journal of Biological Sciences, 2025)
Ice-ice disease remains a major threat in the cultivation of the seaweed Kappaphycus alvarezii, often causing massive crop failures due to a failure to adapt to environmental stress. This study aims to systematically review the physiological responses and metabolite changes of Kappaphycus alvarezii during the transition from a healthy state to an infected phase. A Systematic Literature Review (SLR) was conducted by analyzing 21 scientific articles from Google Scholar, PubMed, Scopus, Sinta, and Portal Garuda databases published between 2016 and 2026. The data synthesis reveals that abiotic stress, particularly sea surface temperatures above 30°C and salinity below 30 ppt, triggers the overproduction of Reactive Oxygen Species (ROS), leading to the degradation of photosynthetic pigments and excessive excretion of organic mucus. This weakening of host defenses triggers a microbiome shift from beneficial endophytic bacteria (Bacillus, Halomonas) to opportunistic pathogens (Vibrio, Actinobacillus) that degrade cell walls through agarase enzymatic activity. Although destructive, NPK nutritional intervention through the luxury consumption method, modification of planting depth, and the application of natural antibacterials have proven effective in stimulating tissue regeneration. This study concludes that ice-ice disease is fundamentally a manifestation of physiological failure that can be mitigated through precise environmental management and technology-based early detection.